A Simple, Fast, and Inexpensive Simultaneous Determination of Trace Bismuth(III) and Lead(II) in Water Samples by Adsorptive Stripping Voltammetry - Malgorzata Grabarczyk; Marzena Adamczyk (Journal of Analytical Methods in Chemistry)
A simple, fast, and inexpensive voltammetric method for the simultaneous determination of trace bismuth(III) and lead(II) using (Hg(Ag)FE) as a working electrode was optimized. For adsorptive stripping voltammetric determination of Bi(III) and Pb(II) in a single scan, the cupferron was applied as a complexing agent. Experimental conditions under which these elements can be simultaneously detected include 0.1 mol L−1 acetate buffer (pH = 4.6), 1 × 10−4 mol L−1 cupferron, accumulation potential −0.05 V, and accumulation time 30 s. The experiments were performed without deaeration of the solutions. The calibration graph was linear from 2 × 10−9 mol L−1 to 1 × 10−7 mol L−1 for the simultaneous presence of bismuth and lead. The detection limits for preconcentration time of 30 s were 6.7 × 10−10 mol L−1 and 8.8 × 10−10 mol L−1 for bismuth and lead, respectively. The application of this procedure was tested by analyzing certified reference material (SPS-WW1 Wastewater) and Lake Zemborzyce water (eastern areas of Poland).